PERJANJIAN KREDIT PERBANKAN MIKRO DALAM PERSPEKTIF PELINDUNGAN HUKUM TERHADAP NASABAH - PRASETYANTO, DIDIK (2011)
Micro, small and medium enterprises (UMKM) have a strategic role. To support these activities are banking has an important role in supporting the UMKM capital in order to develop the business. Implementation of lending to UMKM should go through the credit agreement in this case has been classified by the bank, so customers have a low bargaining position. Should the content of credit agreements must contain clauses that could provide legal protection of creditors and debtors, so that both will be mutually beneficial. This study aims to determine: (1) the factors which could result in disputes between banks and customers, (2) protection efforts for customers of the risks that arise in the micro- credit agreement, and (3) conformity clauses in credit agreements micro by Act No. 8 of 1999 on Consumer Protection. This research used juridical -normative (juridical empirical) with descriptive analytical approach. This study examined using literature studies using primary legal materials, secondary and tertiary as well as using interviews to obtain a picture of consumer protection against micro-credit clients in banking in Surakarta. Analysis of data using qualitative methods. Based on this study concluded that: (1) The problems which could result in disputes between banks and customers in micro-credit agreement in Surakarta include: differences in the recording schedule loan payments, credit costs that must be paid to customers and changes in interest rates at any time in accordance with Indonesian bank interest, and the right to unilaterally terminate the agreement by the bank, (2) protection efforts for customers of the risks arising in micro-credit agreement at the time of the loan agreement is the protection of the contents of the credit agreement. Protection efforts after the credit agreement is with customer complaints and mediation services, (3) clauses in the loan agreements do not include elements of legal protection for bank customers in accordance with Law No. 8 of 1999 on Consumer Protection. The bank argued that such clauses based on the strict attitude of banks to implement the principle of prudence in lending / financing. The bank in implementing Article 18 of the Basic Forestry Law is to give sufficient warning to clients the existence and enactment of important clauses in the agreement, the notification made on or before the signing of loan agreement / financing, formulated in words and sentences are clear, and provide adequate opportunity for the debtor to know the contents of the agreement.